Teaching Prison Abolition to Criminology Students: Critical Reflections on a Pedagogy of De-Initiation - Catello, Roberto (Critical Education, 2025)
The abolitionist movement is gaining momentum in the United States and the United Kingdom and calls to shrink the carceral state have become a staple of grassroots movements and activist groups fighting for a more just world in the 21st century. The role played by higher education (HE) educators in this struggle for a world without prisons is an important and yet difficult one, as they can expose university students to abolitionist ideas but have to do so in the context of a HE sector that is increasingly governed by neoliberal logics of marketization and professionalization. In this article, I reflect on my own experience teaching prison abolition to criminology students at Liverpool Hope University (LHU). The article revisits Richard Stanley Peters’ notion of education as initiation to show how an abolitionist pedagogy grounded in critical perspectives on punishment can be practiced to de-initiate students from two problematic mindsets that criminological education tends to produce: that of guardians of order and internal critics.